БЮДЖЕТНА ДЕЦЕНТРАЛІЗАЦІЯ: ПЕРЕДУМОВИ ТА НАПРЯМИ РЕАЛІЗАЦІЇ (Світ фінансів, 2017)
Далєвська Т. А. Бюджетна децентралізація: передумови та напрями реалізації. Досліджено передумови реалізації бюджетної децентралізації в Україні. Проаналізовано систему фінансового забезпечення місцевого самоврядування на прикладі місцевих бюджетів Вінницької області. Визначено, що до 2014 р. місцеве самоврядування в Україні характеризувалося значним рівнем фінансової залежності від центральної влади, що мало свій прояв у зростанні частки офіційних трансфертів в доходах бюджетів базового рівня, низькій питомій вазі власних доходів та обмеженості видаткових повноважень місцевої влади. Запропоновано ключові напрями бюджетної децентралізації, які підвищать ефективність її реалізації. Далевская Т. А. Бюджетная децентрализация: предпосылки и направления реализации. Исследованы предпосылки реализации бюджетной децентрализации в Украине. Проанализирована система финансового обеспечения местного самоуправления на примере местных бюджетов Винницкой области. Определено, что к 2014 г. местное самоуправление в Украине характеризовалось значительным уровнем финансовой зависимости от центральной власти, имело свое проявление в росте доли официальных трансфертов в доходах бюджетов базового уровня, низком удельном весе собственных доходов и ограниченности расходных полномочий местной власти. Предложены ключевые направления бюджетной децентрализации, которые повысят эффективность ее реализации. Dalevska T. Fiscal decentralization: background and areas of implementation. Introduction. Today in Ukraine is not satisfied the main purpose of the local government, which consists in supporting economic development of the local community and sufficient living standards. In 2015, it became necessary to increase the effectiveness of the system of financial support of local governments on principles of fiscal decentralization.Purpose. Researching of the system of local government financial support and identifying ways of increasing the efficiency of fiscal decentralization in Ukraine.Results. Independence and self-sufficiency of local authorities are declared in basic legislative and regulatory acts of Ukraine. However, by 2014 the budgets of local governments in Ukraine was characterized by low levels of financial independence. The share of official transfers for the period 2005–2014 years rose to 56% of local revenue. In the structure of Vinnitsa region local budgets’ revenues in 2004–2014 dominated tax revenues (44%), the share of official transfers was 30%. However, in structure of official transfers dominated tied transfers (the share of subsidies was 27,6%, against 65% in region’s and districts’ budgets). The share of Vinnitsa region local budgets, volume of which are determining by local governments, is not exceed 0,68% and averaged amounted to 0,24% in GRP for the period 2004–2014.Conclusion. Results of the analysis show that in 2015 the fiscal decentralization coefficients increased significantly, but there is need to improve the process of fiscal decentralization. In particular, it is necessary to agree on certain provisions of the current legislation in terms of strict lines of authority and responsibility; provide the conditions for full use the potential of administrative-territorial unit by local authorities; increase the volume of own revenues in order to finance economic development.